DEVELOPING WRITING ASSESSMENT RUBRIC FOR EXPLANATION TEXT OF GRADE XI STUDENTS AT SMKN 4 MEDAN - Aji Dwi Rayana; Rahmad Husein; Anggraini Thesisia Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
Writing is one of skills in English and it’s important for students, also it is not an easy skill to master. As stated by Richards and Renandya (2002: 303), writing is the most difficult skill to master for second or foreign language students. Writing skills are placed in the last section after three skills namely listening, speaking, and reading. It can be said that students must apply everything they have in the previous three stages. This study aims to develop a writing assessment rubric for explanation text for eleventh grade, to assess student writing related to the availability of the 2013 Curriculum for English subjects in the school. This research is about how and why, which is the process of explanation text itself and at the same time can improve their writing skills. This research method uses research and development methods (R&D). It is hoped that by using reliable rubrics, teachers can easily assess the writing performance of their students who meet the requirements of the writing aspects. The expert gives some corrections and suggestions on the development writing assessment rubric. Based on the result of the writing assessment rubric, the average was 3,7 and the percentage was 93,7% that categorized in “Very Good” category.Keywords: Assessment Rubric, Students’ Explanation Text, Writing